Material management in themed restaurants: inspiring the experience economy - Che Ishak, Farah Adibah; Crang, Philip; Abdul Karim, Muhammad Shahrim (Penerbit Universiti Teknologi MARA (UiTM) Malaysia, 2017)
In tune with wider ideas of an experience economy, the hospitality industry has increasingly focused less on giving a service to its customers and more on offering them memorable, sensory experiences. This paper looks at one facet of this provision of experiences: the material engineering and management of the ‘affective atmosphere’ or ‘ambiance’ of a venue. It unfolds the exploration of theme restaurants in practicing the material management as an inspiration to stage an experience. This paper illustrates its arguments through one case study: the Indonesian theming of the Pondok Malindo restaurant, Selangor. Practically, the findings suggest that creating the desired ambiance needs proper planning and careful attention to a wide range of material elements. More broadly, the paper suggests that accounts of the experience economy should consider the powers and agencies of materials and objects.